2011
DOI: 10.5539/ijef.v3n6p135
|View full text |Cite
|
Sign up to set email alerts
|

Spillover Effect of Chinese Cross-Listed Companies across Shanghai, Hong Kong and US Markets

Abstract: This paper assesses the spillover effect of returns of ten Chinese cross-listed equities which are traded in Shanghai, Hong Kong and US markets simultaneously. We find a strong unidirectional spillover effect from US market to Shanghai market, however, a significant two-way influence exists between Hong Kong and US markets. When we use VAR modeling to exam the same-day effect, we find evidence that the effect of same-day return occurs from the Shanghai to Hong Kong market and from the Hong Kong to US market; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, Creators is facing the risk of leakage of creativity in this process. Once the secret or main technology is leaked, it means that the whole project is failed [2].…”
Section: Risk Analysis Of Crowdfunding Financingmentioning
confidence: 99%
“…However, Creators is facing the risk of leakage of creativity in this process. Once the secret or main technology is leaked, it means that the whole project is failed [2].…”
Section: Risk Analysis Of Crowdfunding Financingmentioning
confidence: 99%
“…They found that the price differential among the shares was caused by the country-specific risks related to the Chinese stock market among the three groups of investors. Li, Yi, & Su (2011) also investigated the spillover effect of the returns of cross-listed Chinese stocks that are traded simultaneously in the Shanghai, Hong Kong, and U.S. markets. They reported a strong, unidirectional spillover effect from the U.S. market to the Shanghai market.…”
Section: Literature Review On the Discount Puzzles In The Chinese Stomentioning
confidence: 99%